Characterization of the Immune Inflammatory Profile in Obese Asthmatic Children - Magrone, Thea; Simone, Maria; Altamura, Maria; Munno, Irene (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
Asthma and obesity are two common disorders often associated in children and characterized by an inflammatory status. Growing evidences support a connection between obesity and asthma since weight reduction can improve asthmatic symptoms. In this study, we have enrolled eighty children: 17 non asthmatics and non obese, 19 obese, 28 asthmatics-obese and, 16 asthmatics non-obese, respectively. In all participants, respiratory functional tests and body mass index (BMI) were calculated. Moreover, systemic inflammation of biomarkers such as T helper (h)1-type, Th2-type and T regulatory-type serum cytokines along with major adipokines was determined. Data will show that the association between asthma and obesity leads to a predominant Th1-type response with an increase in pro-inflammatory cytokines. This inflammatory profile in asthmatics-obese children is sustained by elevated serum levels of leptin and visfatin, while adiponectin concentration is rather diminished. Finally, levels of systemic inflammatory biomarkers positively correlate with the increase in BMI values in all population subgroups.
Keywords: leptin